1999
DOI: 10.1016/s0895-7061(98)00260-x
|View full text |Cite
|
Sign up to set email alerts
|

Benidipine stimulates nitric oxide synthase and improves coronary circulation in hypertensive rats

Abstract: We evaluated the effects of long-term treatment with benidipine, a long-acting calcium antagonist, on endothelial cell-type nitric oxide synthase (eNOS) activity and eNOS mRNA expression in the left ventricle (LV) and its relation to coronary flow reserve, and microvascular remodeling in renovascular hypertensive rats (RHR: 2K-1C Goldblatt). Benidipine (5 mg/kg/day) was given to RHR (B-RHR, n = 11) for 6 weeks. Vehicle-treated RHR (U-RHR, n = 11) and age-matched sham-operated rats (ShC, n = 11) served as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 41 publications
3
33
2
3
Order By: Relevance
“…12 The ability of benidipine to inhibit MDMP generation provides additional evidence of the antiatherosclerotic action of this drug. 22,34,35 The reduction in circulating levels of chemokines and adhesion molecules following benidipine administration provides confirmatory data and is consistent with the observed improvement in endothelial infarction. 22,23 In particular, it suggests that benidipine is effective for vascular disorders that involve oxLDL, since the effect of this drug was significant in diabetes patients with high levels of anti-oxLDL antibody.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…12 The ability of benidipine to inhibit MDMP generation provides additional evidence of the antiatherosclerotic action of this drug. 22,34,35 The reduction in circulating levels of chemokines and adhesion molecules following benidipine administration provides confirmatory data and is consistent with the observed improvement in endothelial infarction. 22,23 In particular, it suggests that benidipine is effective for vascular disorders that involve oxLDL, since the effect of this drug was significant in diabetes patients with high levels of anti-oxLDL antibody.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, the effect of benidipine on monocytes and endothelial cells described above might be independent of the antihypertensive effect. 22,23,25,[34][35][36] Various factors are involved in diabetic vascular change, one of which is monocyte/macrophage migration. 16,[37][38][39][40] Migration of monocytes into the vascular subendothelium occurs during the inflammatory response and plays a key role in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, данная группа препаратов эффек-тивно ингибирует вызванную эндотелином вазокон-стрикцию именно на этом уровне. Показано, что лечение нифедипином приводит к увеличению плот-ности капиллярной сети в миокарде, а терапия блока-торами кальциевых каналов длительного действия (бенидипин), кроме того, способствует нормализа-ции отношения просвет/стенка в артериолах мио-карда левого желудочка [14].…”
Section: Results Therapy With Prestansunclassified
“…Previous studies using animal models have demonstrated that benidipine increases endothelial NO synthase gene expression and enhances NO production. [26][27][28] A recent study has shown that benidipine improves decreases in tetrahydrobiopterin, an essential cofactor of NO synthase, in the plasma and kidneys, leading to reduction of proteinuria in a rat model of type II diabetes. 28 Preservation of tetrahydrobiopterin levels by benidipine may be partly involved in enhancement of NO production.…”
Section: Discussionmentioning
confidence: 99%